2023
DOI: 10.3390/microorganisms11122966
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fungicide Combinations for Overcoming Plasmopara viticola and Botrytis cinerea Fungicide Resistance

Junrui Zhang,
Jhulia Gelain,
Guido Schnabel
et al.

Abstract: Fungal diseases, including downy mildew (caused by Plasmopara viticola) and gray mold (caused by Botrytis cinerea), significantly impact the marketable yield of grapes produced worldwide. Cytochrome b of the mitochondrial respiratory chain of these two fungi is a key target for Quinone outside inhibitor (QoI)-based fungicide development. Since the mode of action (MOA) of QoI fungicides is restricted to a single site, the extensive usage of these fungicides has resulted in fungicide resistance. The use of fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Specially, the down-regulation of lipid metabolismrelating genes in the comparison NI-(Pd-d/Pd-wt), including fatty acyl-CoA oxidase-encoding gene and carnitine acetyl transferase-encoding gene (Table 2), was also reported in Pisolithusmicrocarpus and Beauveria bassiana [76,77]. And the down-regulation of energy metabolismrelating genes in the comparison NI-(Pd-d/Pd-wt), including cytochrome b-encoding gene and ATP synthase-encoding gene (Table 2), was also reported in Botrytis cinerea and Corynespora cassiicola [55,78]. Thus, even in the absence of fungicide, there has been an association of Pdmfs2 with multiple metabolisms required in the fungi adaptation to their growth environments, and such an adaptation might be one aspect of the physiological basis to develop fungicide resistance.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Specially, the down-regulation of lipid metabolismrelating genes in the comparison NI-(Pd-d/Pd-wt), including fatty acyl-CoA oxidase-encoding gene and carnitine acetyl transferase-encoding gene (Table 2), was also reported in Pisolithusmicrocarpus and Beauveria bassiana [76,77]. And the down-regulation of energy metabolismrelating genes in the comparison NI-(Pd-d/Pd-wt), including cytochrome b-encoding gene and ATP synthase-encoding gene (Table 2), was also reported in Botrytis cinerea and Corynespora cassiicola [55,78]. Thus, even in the absence of fungicide, there has been an association of Pdmfs2 with multiple metabolisms required in the fungi adaptation to their growth environments, and such an adaptation might be one aspect of the physiological basis to develop fungicide resistance.…”
Section: Discussionmentioning
confidence: 81%
“…According to studies in the past years, more and more evidence has emerged to support comprehensive metabolism backgrounds underlying fungicide resistance. Such backgrounds include various ERG-encoding genes in fungal ergosterol biosynthesis pathways [36,41,42], acetyl-CoA carboxylase (ACCase)-encoding genes in the lipid and fatty acid oxidation path-ways [45][46][47], reactive oxygen species (ROS)-metabolizing enzyme-encoding genes in the cell wall maintenance and oxidative-stress-responsive processes [50,51], mitochondrial respiratory chain protein-encoding genes in the cellular energy metabolisms [53][54][55], ubiquitin-encoding genes in the post-translational modification processes [57][58][59], and protein kinase-encoding genes involved in mitogen-activated signal transductions [55,60,61]. In the present study, RNA-seq analysis revealed that Pdmfs2 knockout led to the down-regulation of genes involved in peroxisome (ko04146) and oxidative phosphorylation (ko00190) at no prochloraz treatment (Tables 1 and 2, and Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation